Probiotic Effects of Bacillus licheniformis DSM5749 on Growth Performance and Intestinal Microecological Balance of Laying Hens - Pan, Xue; Cai, Yuanli; Kong, Linglian; Xiao, Chuanpi; Zhu, Qidong; Song, Zhigang (Frontiers in Nutrition, 2022)
This study was conducted to investigate the effects of Bacillus licheniformis DSM5749 on the production performance and intestinal health in laying hens. A total of 32-week-old laying hens (Hyline Brown) were randomly assigned to two dietary groups (10 replicates of 27 laying hens), namely, basal diet and basal diet complemented with 200 g/t B. licheniformis (3.2 × 109 CFU/kg). The trial lasted for 8 weeks, and samples were collected at the last week. Results revealed that B. licheniformis DSM5749 significantly improved laying performance, including an increase in egg production rate and average daily egg yield, and a decrease in the feed-to-egg ratio during the entire 8-week experimental period (P < 0.05). B. licheniformis DSM5749 increased the levels of superoxide dismutase and glutathione peroxidase in the liver and decreased the IL-1 level in the serum (P < 0.05). In addition, the integrity of intestinal morphology (villus height, crypt depth, and villus height/crypt depth), tight junctions (ZO-1, Claudin-1, and Occludin), and lipase vitality in the intestine were potentiated by B. licheniformis DSM5749 in laying hens (P < 0.05). B. licheniformis DSM5749 decreased the Firmicutes/Bacteroidetes ratio (P < 0.05) in the cecum. Furthermore, B. licheniformis DSM5749 modulated the microbiota in the cecum of the laying hens, increased the relative abundance of beneficial bacteria (e.g., Prevotella) at the genus level and decreased the relative abundance of potential pathogens (e.g., Desulfovibrio). In conclusion, B. licheniformis DSM5749 can improve laying performance, promote intestinal health, affect the composition of cecal microorganisms, and regulate the intestinal micro-ecological balance, making B. licheniformis a good probiotic candidate for application in the laying hens industry.